Route optimization for solid waste collection: Trabzon (turkey) case study - Apaydin, O.; Gonullu, M. T. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2007)
In a municipal solid waste management system, decreasing collection/hauling costs, which consist of 85% of total disposal expenditure, can be carried out by a route optimization. Thus, a huge amount of economical benefits is getting furnished. If route optimization is performed in solid waste collection/hauling process, due to reductions in empty miles negativity, total expenditures will be decreased. Trabzon City located in the northeast side of Turkey has about 185 thousand inhabitants according to Census 2000. The city shares just about 1% of the Gross Domestic Income in Turkey. In other words, that means that Trabzon City livings have moderate revenue. The objectives of this study are to optimize for the route of collection/hauling in Trabzon City by taking consideration of data about road net, demographics and solid waste production. In order to analyse the solid waste collection/hauling process in the city, the processes were recorded by a Sony DCR-TRV145E brand video camera. To use route optimization process, data related in present spending, truck type and capacity, solid waste production, number of inhabitants and Global Positioning System (GPS) receiver data for each route were collected and all the data were analyzed with each other. For 39 districts in the city, a shortest path model was used in order to optimize solid waste collection/hauling processes, as minimum cost was aimed. The Route View ProTM software as an optimization tool was used for that purpose. Geographic Information System (GIS) elements such as numerical pathways, demographic distribution, container distribution and solid waste production amount were integrated to the software. To give an idea, thematic container layer has 777 container location points for the entire city. After performing routes by the software, the optimized routes were compared with the present routes. Success by the optimization process was around 4-59 % for distance and 14-65 % for time. Consequently, a route optimization process on the street stationary container collection system will contribute a benefit by 24 % in total cost.
Keywords: GIS; Trabzon City; route optimization; solid waste; collection/hauling; Environmental Sciences & Ecology